2020
DOI: 10.1007/s00269-020-01113-7
|View full text |Cite
|
Sign up to set email alerts
|

High-temperature study of basic ferric sulfate, FeOHSO4

Abstract: We report in this paper a new crystal-chemical study of synthetic basic ferric sulfate FeOHSO4. The structure solution performed by the Endeavour program, from new X-ray powder diffraction (XRPD) data, indicated that the correct space group of the monoclinic polytype of FeOHSO4 is C2/c. Selected Area Electron Diffraction (SAED) patterns are also consistent with this structure solution. The arrangement of Fe and S atoms, based on linear chains of Fe3+ octahedra cross-linked by SO4 tetrahedra, corresponds to tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 33 publications
3
15
1
Order By: Relevance
“…Similar results were obtained by combining X-ray diffraction and infrared analyses in Safiullin et al [22]. FeOHSO 4 was also observed after X-ray refinement of a synthetic FeSO 4 •7H 2 O sample heated at 300 • C for 24 h [23] and at 280 • C for 7 days [24].…”
Section: Introductionsupporting
confidence: 86%
See 3 more Smart Citations
“…Similar results were obtained by combining X-ray diffraction and infrared analyses in Safiullin et al [22]. FeOHSO 4 was also observed after X-ray refinement of a synthetic FeSO 4 •7H 2 O sample heated at 300 • C for 24 h [23] and at 280 • C for 7 days [24].…”
Section: Introductionsupporting
confidence: 86%
“…The three-step dehydration process entails the formation of FeOHSO 4 as also observed in synthetic samples [21,23,24]. However, our structural analysis provides further details on the stability of the FeOHSO 4 phase, which in fact resulted to be the predominant product of the entire decomposition process, as it was refined in the patterns collected from 100 to 475 • C (Figure 7).…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Even though the XRD measurement indicated that no other phases than the basic ferric sulfate-arsenates existed, their presence in a small amount under the detection limit could not be excluded (Figure 1). e FeSAsOH structure is constructed from layered Fe-O 6 octahedra that are cross-linked by AsO 4 and SO 4 tetrahedra (Figure 7) [4,9,18]. For the dissolution of the basic ferric sulfate-arsenate [FeSAsOH-1] at pH ≥2, the gradual decrease in solution pH indicated an OH − depleting.…”
Section: Dissolutionmentioning
confidence: 99%